Ciudadanía y medio ambiente - Dobson, Andrew (Colección Siglo XXI (Editorial Proteus), 2012)
In this text, Andrew Dobson argues that ecological citizenship cannot be fully articulated in terms of the two great traditions of citizenship - liberal and civic republican - and develops an original theory of citizenship, which he calls 'post-cosmopolitan'.